Evaluation of the Lyophilized MIBI Kit Fraction for 99mTc Labeling: A Cost-Effective Approach for Labeling Cold Kits in Nuclear Medicine Practice - Islam, Sanjida; Azim, Mohammad Anwar Ul; Uddin, Md Jashim; Biswasarma, Sanchoy Chandra; Islam, Md Saiful; Mandal, Tapati; Mamun, Mustafa; Khatun, Shakera; Islam, Md Saiful; Banu, Most Layla Saroware (Bangladesh Journal of Nuclear Medicine, 2024)
99m-Technetium methoxy isobutyl isonitrile (MIBI) is one of the most commonly utilized radiopharmaceuticals for Myocardial Perfusion Imaging (MPI) and parathyroid scan. Typically MIBI kits contain substantial amounts of reagents suitable for labeling multiple doses of radiopharmaceuticals. The conventional practice of preparing only 1-2 doses from a single vial often results in significant wastage of the kit’s contents. To mitigate this inefficiency, we explored the feasibility of fractionating cold kits. The MIBI kits underwent a systematic fractionation process, with precise ratios of 1:2 and 1:4. Total eight samples of each ratio were analyzed. The average percentage RCP for eight samples with a 1:2 ratio was determined to be approximately 93.87%, while for eight samples with a 1:4 ratio, it was found to be around 89.045%, as assessed using the TLC method. Normal biodistribution patterns were observed in imaging conducted with various samples of 1:2 ratio fractions. However, there were two reported cases of failure in biodistribution for a fraction with 1:4 ratio. Using this standardized technique for the fractionation of cold kits proves to be a cost-effective approach, minimizing the wastage of chemical components in cold kits. Bangladesh J. Nuclear Med. 26(2): 188-192, 2023